Basins of Attraction of an Anti-competitive Discrete Rational System
We investigate the global asymptotic behavior of solutions of the following anti-competitive system of difference equations equation* x_n+1=γ _1y_n A_1+x_n , y_n+1=β _2x_n+γ _2y_n y_n , n=0,1,…, equation* where the parameters γ _1,γ _2,β _2,A_1 are positive numbers and the initial conditions x_0≥ 0,y_0>0. We find the basins of attraction of all attractors of the system, which are the equilibrium point and period-two solutions. 2000 Mathematics Subject Classification. 37E30, 37G99, 39A10, 39A11 , number=2, journal=Sarajevo Journal of Mathematics, author=Nurkanović, Mehmed and Nurkanović, Zehra, year=2024, month=Jun., pages=259–272